Acridone alkaloids from the rhizomes of Luvunga scandens (Roxb.) Buch. Ham. Issue 15 (3rd August 2019) - Tran, Nguyen Minh An; Do, Thi Hong Tuoi; Truong, Luu Hong; Le, Dung Tien; Phan, Minh Nhat; Pham, Nguyen Kim Tuyen; Mai, Dinh Tri; Nguyen, Tan Phat
Abstract: The ethyl acetate extract of the rhizomes of Luvunga scandens (Roxb.) Buch. - Ham. ex Wight & Arn (Rutaceae) delivered one new acridone alkaloid named Luvungaside A (1 ) together with three known acridone alkaloids, namely 1, 3-dihydroxy-2-methoxy-10-methyl-9-acridone (2 ), arborinine (3 ) and 1-hydroxy-3-methoxy-10-methyl-9-acridone (4 ). Compounds were reported for the first time from the species L. scandens applying various chromatography methods. Chemical structures were elucidated by IR, UV, HR-ESI-MS, NMR 1D & 2D experiments and comparison with the literature. The cytotoxicity and hepatoprotective activity of compounds1 –4 in human hepatoma cell line HepG2 was measured by MTT assay. At 10–100 μM, compounds expressed significant hepatoprotective effect with prevention percentage ranging from 81.1% to 194.3%, compared to the positive control quercetin displaying 49.0%. Graphical Abstract: